SENSORY PROPERTIES OF ANALOG COFFEE FROM BANANA PEELS - Umar Hafidz Asy'ari Hasbullah; Allikha Bias Mentari; Siti Nur Kholisoh; Taufik Nor Hidayat (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Banana peel had the potential to be used as analog coffee. The sensory of analog coffee will determine consumer acceptance and potential for production. This research aims to study the effect of banana peel maturity and the length of the oven on the sensory characteristics of banana peel analog coffee. Ripe and unripe Kepok banana peels were dried and then baked in the oven with time variations of 5, 10, and 15 minutes/ 50 gram. Then it was reduced in size and sieved with 60 mesh. The sensory test was used hedonic were performed by untrained panelists and descriptive methods were performed by the first training panelists. The results were showed that the panelists' preference towards color and aroma of analog coffee powder increased with the length of baking time. The preference for ripe banana peel analog coffee was greater than that of unripe banana peel. The panelists' preference for the color, aroma, and taste of brewed analog coffee was increased with longer baking time. The flavor of brewed analog coffee of ripe banana peel was stronger than that of the unripe peel. The most preferred banana peel coffee was ripe banana peel baked at 180°C for 15 minutes. It was showed characteristics of darker color and a stronger aroma of coffee powder. The most preferred brewing analog coffee was that with the darkest color, the coffee's strongest aroma, and the strongest bitter taste.